Mathematical programming : theory and methods - Sinha, S. M. (Elsevier, 2006)
Mathematical Programming, a branch of Operations Research, is perhaps the most efficient technique in making optimal decisions. This self-contained book is an overview of mathematical programming from its origins. It is suitable both as a text and as a reference.